Developing a Business Application with BPM and MDE - Fernández-Fernández, Héctor; Palacios-González, E.; García-Díaz, Vicente; Pelayo García-Bustelo, B. Cristina; Sanjuán Martínez, Óscar; Cueva Lovelle, Juan Manuel (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2019)
In this paper we have designed an architecture for the generation of a business application, that allows to business users to adapt their processes to the constant change. At the moment all the architectures based to a great extent on SOA allow to modify the processes in a short period of time, but we go beyond and give the possibility to the business user of modifying their processes. To design this architecture, we rely on the fundamental use of two technologies: BPM (Business Process Modeling) and MDE (Model Driven Engineering). Inside these technologies we focus on the creation of a business process notation extended from BPMN that is agile, easy to learn and design, and capable to provide semantic information about the process. Therefore this notation allows business process to modify their processes to achieve the proposed goal.
Keywords: Atlas Transformation Language (ATL); Business Process Modeling Notation (BPMN); XML Process Definition Language (XPDL); Model Driven Engineering (MDE); IJIMAI